Effectiveness and mechanisms of action of Bacillus velezensis GUMHT p116 against major fungal pathogens causing postharvest soft rot in kiwifruit - Xueping Wu; Zhu Li; Jianjun Lin; Zhanmei Li; Minjie Zhou; Minwei Xiang; Youhua Long; Lijuan Peng; Haixia Ding (Postharvest Biology and Technology, 2026)

Porous-interconnected cell microspheres-based 3D bioprinting of vascularized high-cell-density tissues with channel-pore networks - Xueping Wang; Xinyu Zhang; Lin Gu; Menglin Liang; Yudong Yao; Yuan Jin; Lei Shao (Chemical Engineering Journal, 2026)

Optimal scheduling of mixed conventional and modular autonomous bus fleets for sustainable urban transit - Xueping Dou; Ran Dong; Yuqi Lin; Tongfei Li (Journal of Cleaner Production, 2026)

Extracellular vesicles in cancer progression: mechanisms and significance - Ying Gao; Denghui Wei; Li Zhong; Dan Liao; Xueping Zheng; Yujie Lin; Dongmei Fang; Boyang Chang; Tiebang Kang (Science China Life Sciences, 2026)

The value assessment framework and institutional innovation for implementing the requisition-compensation balance policy of natural coastline in China - Yue Yu; Yanyan Fu; Wei Liu; Degang Jiang; Jingwei Zhang; Xingmin Liu; Xueping Wei; Jing Lin (Frontiers in Marine Science, 2026)
Natural coastlines are vital for ecological security and sustainable development. To mitigate their decline, China has implemented requisition-compensation balance policy (RCBP) for coastlines, adapted from the management of cultivated land. This study systematically reviews the policy’s institutional evolution and highlights fundamental distinctions between coastlines and cultivated land in functional services, spatial heterogeneity, and evaluation standards. While the policy has achieved preliminary success in maintaining quantitative and qualitative balance, several challenges persist. These include the absence of functional equivalence assessment, weak long-term safeguards, underdeveloped cross-regional and market-based coordination mechanisms. These gaps risk leading to “higher-grade requisition, lower-grade compensation” and ecological degradation at compensation sites, and increased administrative burdens. To address these issues, this study develops a comprehensive value-equivalence compensation framework structured around a “three-dimensional and four-layer” indicator system that integrates functional, spatial, and temporal dimensions. It advocates for a strategic transition from quantity-oriented to value-oriented governance. Corresponding policy recommendations are proposed: establishing unified technical guidelines for value assessment, creating a nationwide quota-trading platform to activate market forces, and strengthening post-restoration monitoring for long-term stewardship. This research provides theoretical and practical insights to enhance the protection, restoration and sustainable management of coastlines in China.

Highly linear bionic strain decoupling sensor mediated by curved surface stress - Xueping Zhang; Junqiu Zhang; Jiachao Wu; Yu Chen; Xueyang Li; Wenjie Yu; Xiancun Meng; Guilin Li; Lina Ju; Bo Li; Tao Sun; Zhiwu Han; et al. (Chemical Engineering Journal, 2026)

Environmental impact and carbon footprint analysis of rural domestic wastewater treatment plants based on life cycle assessment method: A case study of Fuzhou City, China - Hanwei Huang; Xiaoying Lin; Junjun Chen; Xueping Liu; Zushan Zhuo; Yuqi Li (Journal of Water Process Engineering, 2025)

Unveiling the yeast interaction: Insights into the role of Saccharomyces cerevisiae metabolites in regulating Torulaspora delbrueckii aroma biosynthesis during wine fermentation - Boqin Zhang; Mengbo Wang; Wenjie Li; Yucui Chen; Xueping Zhao; Chenxi Yu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

The distribution characteristics of marine litter in the intertidal zone of Lvhua Island and its impact on the macrobenthic community structure - Kaiyi Wang; Shuhan Wang; Jianing Sun; Qiao Zou; Jiaming Ou; Li Li; Shouyu Zhang; Xueping Lin; Kai Wang (Marine Environmental Research, 2025)

Overexpression of cucumber CsVQ12 gene modulates MeJA-mediated freezing tolerance and leaf senescence in Arabidopsis - Feng Yang; Hailin Xia; Jindong Zhao; Xueping Guo; Meng Wang; Ziyu Lin; Dongdong Mao; Zhaoyang Hu; Yuelong Zhou; Shiqiang Liu; Yong Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

An efficient network with state space model under evidential training for fetal echocardiography standard view recognition - Changzhao Chen; Yiman Liu; Tongtong Liang; Shibin Lin; Xiaoxiang Han; Xiaohong Liu; Jing Yang; Yuqi Zhang; Xueping Yan (Medical & Biological Engineering & Computing, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Mapping the research framework and key trends of coral reefs in the South China Sea - Junhui Chen; Fei Tang; Heshan Lin; Bo Huang; Xueping Lin (Frontiers in Marine Science, 2025)
The South China Sea, a key biodiversity hotspot in the Central Indo-Pacific, hosts a rich array of coral reef species and marine life but faces growing threats from climate change and human activities. This study systematically analyzes coral reef research in the region using a bibliometric analysis of records from the Web of Science Core Collection. The analysis highlights the diverse roles of contributing countries and their collaborations, with China emerging as a significant contributor to the regional scientific output. Our findings categorize the research into five principal themes through text mining and bibliographic coupling: (1) fundamental physical-biological interactions within reef systems, (2) biodiversity and symbiotic relationships in response to environmental stress, (3) climatic influences and the adaptive responses of reef systems, (4) conservation strategies and management practices for reef resilience, and (5) remote sensing and algorithmic approaches for reef mapping and monitoring. The discussion addresses regional challenges, outlines the identified research framework, and details key trends in South China Sea coral reef research, thereby providing essential information to guide future development and conservation efforts.

Effect of reaction parameters on thermal liquefaction of corncob with methanol - Lin Zhang; Yikun Xu; Yuxing Zeng; Lujin Li; Yifan Chen; Xueping Song; Chao Feng; Peitao Zhao (Fuel, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

A review: Integration of NIRS and chemometric methods for tea quality control-principles, spectral preprocessing methods, machine learning algorithms, research progress, and future directions - Shengpeng Wang; Clemens Altaner; Lin Feng; Panpan Liu; Zhiyu Song; Luqing Li; Anhui Gui; Xueping Wang; Jingming Ning; Pengcheng Zheng (Food Research International, 2025)

Effect of cultivar and process on the astringency of matcha based on flavonoids-targeted metabolomic analysis - Jinjin Xue; Panpan Liu; Yongquan Xu; Anhui Gui; Xueping Wang; Fei Ye; Lin Feng; Shengpeng Wang; Jing Teng; Shiwei Gao; Pengcheng Zheng (Food Research International, 2025)

Carbon dots recovery from waste streams of hydrothermal process - Lin Zhang; Jing Zhang; Siyu Zhao; Chao Feng; Yanan Lv; Zicong Wei; Peitao Zhao; Xueping Song (Biomass and Bioenergy, 2025)

Lignocellulose degradation and temperature adaptation mechanisms during composting of mushroom residue and wood chips at low temperature with inoculation of psychrotolerant microbial agent - Xueping Tian; Xiaomeng Qin; Xiaojun Jia; Qingyang Lyu; Siqi Li; Linwei Jiang; Lin Chen; Zhiying Yan; Jun Huang (Environmental Pollution, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Immobilization of Phosphorus in Sediment-Water System by Active Capping Plate Under Exogenous Phosphorus Input - Xiaohai Wu; Canyang Lin; Xueping Tang; Weihang Cai; Mazhan Zhuang; Chen Huang; Fei Li; Zhenming Zhou (Water, Air, & Soil Pollution, 2024)

Unlocking the secrets of Qingzhuan tea: A comprehensive overview of processing, flavor characteristics, and health benefits - Panpan Liu; Lin Feng; Jia Chen; Shengpeng Wang; Xueping Wang; Yanna Han; Mengjun Ma; Zhonghua Liu; Pengcheng Zheng (Trends in Food Science & Technology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Morroniside inhibits Beclin1-dependent autophagic death and Bax-dependent apoptosis in cardiomyocytes through repressing BCL2 phosphorylation - Xueping Ke; Shicheng Yu; Shubiao Situ; Zhenqian Lin; Yiqiang Yuan (In Vitro Cellular & Developmental Biology - Animal, 2023)

Silver doped-silica nanoparticles reinforced poly (ethylene glycol) diacrylate/hyaluronic acid hydrogel dressings for synergistically accelerating bacterial-infected wound healing - Lin Huang; Wenqiang Li; Mingtao Guo; Zhiguan Huang; Yuhui Chen; Xueping Dong; Yuhe Li; Lin Zhu (Carbohydrate Polymers, 2023)

Sustainable preparation of lignocellulosic nanofibrils and cellulose nanopaper from poplar sawdust - Wei Liu; Shuya Zhang; Kun Liu; Hongbin Yang; Qingyi Lin; Ting Xu; Xueping Song; Haishun Du; Long Bai; Shuangquan Yao; Chuanling Si (Journal of Cleaner Production, 2023)

Quantification of TOC and TN in reservoir sediments using Fourier transform infrared spectroscopy - Lin Mei; Yihong Yue; Yong Qin; Xueping Chen; Fushun Wang (Soil Ecology Letters, 2022)

Identification of terrigenous and autochthonous organic carbon in sediment cores from cascade reservoirs in the upper stream of Pearl River and Wujiang River, southwest China: lignin phenol as a tracer - Li Gao; Xin Lin; Jun Fan; Ming Yang; Xueping Chen; Fushun Wang; Jing Ma (Acta Geochimica, 2022)

Environmental risks and the potential benefits of nanopesticides: a review - Zhenlan Xu; Tao Tang; Qin Lin; Jianzhong Yu; Changpeng Zhang; Xueping Zhao; Melanie Kah; Lingxiangyu Li (Environmental Chemistry Letters, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Interception, degradation and contributions of terrestrial organic carbon obtained from lignin analysis in Wujiang River, southwest China - Xin Lin; Yujie Wang; Jinhua Zhang; Ming Yang; Xueping Chen; Fushun Wang; Jing Ma (Acta Geochimica, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Effects of nitrogen during nursery stage on flower bud differentiation and early harvest after transplanting in strawberry - Chunyan Wan; Lin Mi; Bingyi Chen; Jinfeng Li; Hengzhi Huo; Jintao Xu; Xueping Chen (Brazilian Journal of Botany, 2018)

Genetic variants influencing lipid levels and risk of dyslipidemia in Chinese population - Huaichao Luo; Xueping Zhang; Ping Shuai; Yuanying Miao; Zimeng Ye; Ying Lin (Journal of Genetics, 2017)

Associations Between PPP1R1B Gene Polymorphisms and Anxiety Levels in the Chinese Population - Hui Ma; Xin Li; Ailu Lin; Zhen Yuan; Jing Zhou; Xueping Yang; Zhengtu Cong; Yinglin Huang; Gang Zhu (Neuroscience Bulletin, 2017)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Cathodic stripping voltammetric determination of chromium in coastal waters on cubic Nano-titanium carbide loaded gold nanoparticles modified electrode - Haitao Han; Dawei Pan; Dongyan Liu; Xueping Hu; Mingyue Lin; Fei Li (Frontiers in Marine Science, 2015)

Co-occurrence patterns of above-ground and below-ground mite communities in farmland of Sanjiang Plain, Northeast China - Lin Lin; Meixiang Gao; Dong Liu; Xueping Zhang; Haitao Wu; Donghui Wu (Chinese Geographical Science, 2014)

Effect of Low-Intensity Pulsed Ultrasound on MMP-13 and MAPKs Signaling Pathway in Rabbit Knee Osteoarthritis - Xueping Li; Jianan Li; Kai Cheng; Qiang Lin; Daxin Wang; Hongfei Zhang; Hengyuan An; Mingxia Gao; Anliang Chen (Cell Biochemistry and Biophysics, 2011)